2010
DOI: 10.2478/s11532-009-0133-9
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the effect of mineralization parameters on determination of metals in Viscum album species

Abstract: An increasing interest in determination of various macro-and microelements in medicinal plants has been observed. The majority of studies are carried out using one mineralization method without any optimization. The present study demonstrates that changes in mineralization parameters can significantly affect the recovery of the elements determined. In the study, the dried plant material was mineralized in 12 ways and iron (Fe), copper (Cu), zinc (Zn), nickel (Ni) and manganese (Mn) levels were determined. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Moreover, there is a general understanding that mineralization is crucial to ensure the high quality of an analytical process and careful optimization of all steps involved is of particular relevance. This issue was further investigated by Walas et al [ 28 ] and Blicharska et al [ 29 ]. In particular, the latter analyzed microwave mineralization protocols for herbal samples using the principal component analysis (PCA) and firmly concluded that all mineralization parameters should be carefully optimized prior to the final digestion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is a general understanding that mineralization is crucial to ensure the high quality of an analytical process and careful optimization of all steps involved is of particular relevance. This issue was further investigated by Walas et al [ 28 ] and Blicharska et al [ 29 ]. In particular, the latter analyzed microwave mineralization protocols for herbal samples using the principal component analysis (PCA) and firmly concluded that all mineralization parameters should be carefully optimized prior to the final digestion.…”
Section: Introductionmentioning
confidence: 99%